An indigo-based polymer bearing thermocleavable side chains for n-type organic thin film transistors1. Issue 20 (28th May 2015) - Guo, Chang; Quinn, Jesse; Sun, Bin; Li, Yuning
<x xml:space="preserve">Abstract</x> A new n-type semiconducting polymer based on indigo with thermocleavable tert-butoxycarbonyl (t-Boc) groups was synthesized and used as an active layer in organic thin film transistors.